Breed trends and effect of breed on sale price of lots of beef calves marketed via video auction - McCabe, Esther Dorice (Kansas State University, 2018)
The United States beef cattle industry is continuously evolving and changing to meet buyer demands while considering environment factors for production. Cow-calf producers make decisions within their herds that impact their profitability. Previous research shows producers can add value to beef calves through management and marketing decisions in areas such as genetics, herd health, and nutrition. It is well documented that there are numerous factors that influence the sale price of beef calves, no matter the venue through which they are sold. Historically, steer calves sold for a greater price compared to heifer calves. Apparent breed composition also influences value of lots of beef calves. Black-hided calves recently sold for a greater sale price than calves of other hide colors due to perceived differences in potential performance. Calves with Bos indicus influence usually sell for a lower price than other breed types. Marketing of beef calves through video auction allows sellers to market lots of calves to a buyer basis nationwide. A national market provides a basis for buyer preferences and potential national trends for changes in characteristics valued by buyers. Evaluation of national breed composition trends can indicate potential changes in the industry. The opportunity to evaluate if and how breed description as described by producers influenced calf sale price from 1995 through 2016 was available through a livestock video auction service. Chapter 1 is a review of the literature and an overview of the beef industry and factors affecting sale price of lots of beef calves. Chapter 2 is an analysis of breed composition influencing sale price for lots of steer calves and lots of heifer calves. Chapter 3 investigates national and regional breed description and sire breed trends over a 23-year period.
Keywords: Beef calves; Breed; Brahman influence; Sale price; Steer and heifer calves; Video auction